Calculation of photoelectron spectra: A mean-field-based scheme - Dinh, P. M.; Romaniello, P.; Reinhard, Paul-Gerhard; Suraud, E. (Physical Review A - Atomic, Molecular, and Optical Physics, 2013)
In a previous work, Pohl have proposed a simple scheme for the evaluation of photoelectron spectra of clusters subject to a laser field by collecting one-particle wave functions at a given measuring point close to absorbing boundaries. The scheme gives reliable results for low and moderate laser fields, but it shows failures for strong laser fields. The formulation relies on the assumption of free-electron propagation close to the boundaries. The laser field, however, can still be active when the first bunches of outgoing electrons reach the measuring point, and therefore the free-particle scenario may not hold anymore in case of high laser intensities. In this paper, hence, we generalize the method by using a model of "free" particles in the presence of an electromagnetic dipole field. Numerical tests show that this generalized scheme reduces to that of Pohl for low and moderate laser intensities, whereas it considerably improves the results of the latter for high intensities, thus extending the applicability of the method. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-07-24